Jean Gerson and the Last Medieval Reformation. By Brian Patrick McGuire. Pp. xviii + 441. University Park, PA: The Pennsylvania State University Press, 2005. isbn 0 271 02705 3 and 02706 1. Hardback 85; paper 30 - Harvey, Margaret (The journal of theological studies, 2006)
This is an excellent book which should go far to persuade students that fifteenth-century churchmen have much of importance to say to us. It is very well written and succeeds in keeping one's interest to the last page, even if, as with the present writer, one does not always agree with the author's generalizations in the last chapter. Professor McGuire presents a very human Gerson who had views on an enormous variety of topics from child abuse to lending money at interest, on most of which he sounds surprisingly modern and flexible. Whilst admitting the problems of penetrating the psyche of a fifteenth-century theologian, Professor Mcguire makes a valiant and often convincing effort to marry the writings with the inner life. He also integrates the vernacular with the Latin works.